The Troubling Influence of Equality in Constitutional Criminal Procedure: From Brown to Miranda, Furman and Beyond - Howe, Scott W. (2001)
This Article identifies and critiques a view of the criminal-procedure clauses in the Bill of Rights that is revealed in Supreme Court decisions after Brown v. Board of Education. Professor Howe argues that the Court has gone astray in constructing these clauses by focusing on equality. He contends that the criminal-procedure clauses are better understood as discrete protections of individual liberty than as reflecting a unified theory or separate theories about equality. Building on this perspective, the Article proposes a reformulation of doctrine in varied realms of constitutional criminal procedure, including police -interrogation, capital sentencing, and administrative searches and seizures. The Article also calls on a more general level for rethinking how judges should implement a call for equality as they regulate criminal procedure under the Constitution. The Fourteenth Amendment directs states to provide equal protection of the laws to all persons, a command that applies to the criminal process. However, equality is a derivative idea in that it always requires an external substantive standard for judging likeness and difference. Consequently, Professor Howe con- tends that even an explicit command of equal treatment can only serve as a rhetorical device, authorizing the judiciary to construct substantive standards regarding governmental con- duct. It is for this same reason that equality has no role under the criminal procedure clauses, even as a rhetorical device; those clauses already call for particularized substantive standards. The Article proposes that judges apply the Bill of Rights and reconstruction amendments in criminal procedure by focusing on substantive standards concerning how government should treat persons. Judges should implement the substantive values embodied in the criminal-procedure clauses. They should impose further protections against discrimination deemed to warrant constitutional proscription through the more open-ended provisions, such as the Equal Protection and Due Process Clauses. However, the resolution of what the open-ended clauses should demand must itself build on the substantive construction given those clauses by the judiciary rather than on anything inherent in the notion of equality